Peningkatan Hasil Belajar Matematika Materi Pecahan Sederhana Melalui Media Kartu Pecahan Di Kelas III SD Negeri Jatiadi 1 Kecamatan Gending Kabupaten Probolinggo - Kastur, Annita; Kurniasari, Kurniasari; Hidayati, Fitria (Konsorsium Dosen Sekolah Tinggi Agama Islam (STAI) Al-Yasini Pasuruan, 2025)
This research aims to improve the mathematics learning outcomes of class III students at SD Negeri JATIADI 1 on simple fractions using fraction cards as media. Fraction card media is used by teachers through a fraction card game. This type of research is classroom action research. This research uses the Kemmis and Mc model. Taggart. The subjects in this research were 24students in class III of SD Negeri JATIADI 1, consisting of 14 male students and 10 female students. The techniques used for data collection are observation techniques and written tests. The research instruments used teacher observation sheets, student observations and written tests. The data analysis techniques used are quantitative descriptive and qualitative descriptive. Based on the results obtained, it can be concluded that: the results of learning mathematics using fraction card media for class III students at SD Negeri Jatiadi 1 have increased in simple fraction material. The increase in cycle I was 23.2% while in cycle II it was 39.3%. This increase was due to explaining the rules of the fractional card game, the teacher provided a simulation of the implementation of the fractional card game. In this way, students can play fractional card games according to the rules of the game